Effects of esketamine and fluoxetine on depression-like behaviors in chronic variable stress: a role of plasma inflammatory factors - Chen, Haixia; Zhao, Xinxin; Ma, Xinxu; Ma, Hongzhe; Zhou, Cuihong; Zhang, Yunyun; Peng, Zhengwu; Xue, Shanshan; Cai, Min (Frontiers in Psychiatry, 2024)
Mounting evidence has identified the rapid and sustained antidepressive and anxiolytic-like effects of esketamine. However, the underlying mechanism of this no-monoamine target rapid-onset antidepressant is still underexplored. Immune-inflammatory pathways and cell-mediated immune activation, mainly including inflammatory cytokines in plasma, play a pivotal role in the pathogenesis of major depressive disorder and are also a potential therapeutic target for MDD. The current study was designed to clarify the role of esketamine on the expression of plasma cytokines in a depressive-like model introduced by chronic variable stress (CVS). In this study, a 21-day consecutive CVS protocol was applied to produce depressive- and anxiety-like behaviors. After the single dose or 7-day repeated administration of esketamine or fluoxetine, the depressive- and anxiety-like behaviors and the expression of inflammatory cytokines in plasma were examined. Both a single dose of esketamine and 7-days repeated fluoxetine administration elicited anti-depressive and anxiolytic effects in mice exposed to CVS. Additionally, CVS produced significant changes in the plasma inflammatory factors, notably increasing the expression of IL-1β, IL-6, IL-8, IL-17A, TNFα, IL-4, IL-9, IL-24, IL-37, IFN-β, and CXCL12, while reducing IL-10 and IL-33. With the administration of esketamine and fluoxetine, CVS-produced inflammatory disturbances were partially normalized. Together, our findings provide a novel insight that acute esketamine treatment could rescue CVS-produced depressive-like and anxiety-like behaviors in mice by normalizing the expression of inflammatory cytokines; this effect was similar to the repeated administration of fluoxetine. These results contributed to the understating of rapid anti-depressant effects elicited by esketamine.